Production of Human Milk Fat Substitutes Catalyzed by a Heterologous Rhizopus oryzae Lipase and Commercial Lipases. (13th November 2013) - Simões, Tiago; Valero, Francisco; Tecelão, Carla; Ferreira‐Dias, Suzana
Abstract: This study aims to produce human milk fat substitutes by an acidolysis reaction between lard and the free fatty acids (FFA) from a fish oil concentrate rich in docosahexaenoic acid, in solvent‐free media. The immobilized commercial lipases from (1) Rhizomucor miehei (Lipozyme RM IM), (2) Thermomyces lanuginosa (Lipozyme TL IM) and (3) Candida antarctica (Novozym 435) were tested as biocatalyst. Also, the heterologous Rhizopus oryzae lipase (rROL), immobilized in Accurel ® MP 1000, was tested as a feasible alternative to the commercial lipases. After 24 h of reaction at 50 °C, similar incorporations of polyunsaturated fatty acids (c.a. 17 mol%) were attained with Novozym 435, Lipozyme RM IM and rROL. The lowest incorporation was achieved with Lipozyme TL IM (7.2 mol%). Modeling acidolysis catalyzed by rROL and optimization of reaction conditions were performed by response surface methodology, as a function of the molar ratio FFA/lard and the temperature. The highest acidolysis activity was achieved at 40 °C at a molar ratio of 3:1, decreasing with both temperature and molar ratio. Operational stability studies for rROL in seven consecutive 24‐h batches were carried out. After the fourth batch, the biocatalyst retained about 55 % of the original activity (half‐life of 112 h).